GAMBARAN TINGKAT PENGETAHUAN KELUARGA TENTANG BAHAYA PEROKOK PASIF DI DUSUN JARANAN PANGGUNGHARJO SEWON BANTUL TAHUN 2015 - Yuliana Fatimah, Eka; -, Maryana; -, Sugeng (LPPM STIKES MUHAMMADIYAH GOMBONG, 2018)
The effects of cigarette smoking are not only borne by those who smoke, but also felt by passive smokers. Passive smokers are more inhale of cigarrette smoke with more particles of a substance. The data of Susenas shows the prevalence of passive smokers in Indonesia amounted to 48,9% or 97.560.002 inhabitans, which consist of 31,88% in men and 66% in women. Surveys shows that more than 90% of active smokers have admitted to smoking in home when they were together with other family members.This research aims to know the description of family's level knowledge about the danger of passive smoker in Dusun Jaranan Panggungharjo Sewon Bantul. The research method used was descriptive survey. The research was done in 2015. The research location was in the village of Jaranan, Panggungharjo Sewon Bantul, Yogyakarta. Subjects of this research were members of the family in Jaranan, Panggungharjo, Sewon Bantul who become passieve smokers with productive age (15 – 64 years old) as many as 71 people. This research used proportional random sampling. The research instrument was a questionnaire of 30 statements. Data were analyzed using frequency distribution. In this research showed that 64,7% of respondent were aged over 31 years, 43,6% of respondent had a recent education junior high school,54,92% were housewifes, 93,36% of respondent got the smoke at home, and 64,78% of respondent were inhaled cigarette smoke average <1 hour. From data processing obtained results of the research showed family's level knowledge about the danger of passive smoker was good by 51 respondent (71,8%), qiute as much as 20 respondent (28,2%), and no respondent who had less knowledge level. The description of family's level knowledge about the danger of passive smoker in Dusun Jaranan Panggungharjo Sewon Bantul was in good categories (71,8%). Key word : family, knowledge, the dangers of passive smokers